The intestinal ultrasound role in inflammatory bowel disease in clinical practice and a critical appraisal of the current guidelines (mini-review) - Sarah El-Nakeep (SpringerOpen, 2024)
Abstract Background Intestinal ultrasound (IUS) is a beneficial tool in the diagnosis and follow-up of patients with inflammatory bowel disease. IUS has long been established in monitoring of Crohn's disease patients. Recent studies and guidelines show similar benefits in ulcerative colitis patients. Aim To assess the recent guidelines and the effectiveness and practicality of using IUS in the clinical settings. Methods To assess the role of IUS in different guidelines, a search on the PubMed and Cochrane Library databases was conducted using the following keywords: inflammatory bowel disease, guidelines, and intestinal ultrasound-in addition to a search conducted on national and international guideline sites on the use of IUS in IBD. Related references on the topic were examined by a manual separate search. Results A discussion of the results of different guidelines was conducted regarding the role of IUS in IBD. Conclusion IUS is a very useful tool in IBD diagnosis and follow-up in the clinical settings. There are some areas that have not been yet validated when compared with other established standard diagnostic tools such as endoscopy, histopathology, or other radiological methods. This makes incorporation into the guidelines in its primary stages, added to the different geographical-dependent experience, and availability of the specialty practitioners. Point-of-care management and learning curve for young practitioners are still areas of debate in clinical practice.